ANALISIS SPASIAL DEMAM BERDARAH DENGUE DI PROVINSI SUMATERA SELATAN - Hamzah Hasyim (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Dengue Haemorrhagic Fewer (DHF) has emerged as an inmportant publict health problem, with extensive inclined, follow the mobility increasing, population density with the follow cycle pattern cases. Beside dengue virus strain, DHF cases contribution influenced climatic determinants in spatial scope like climatic factors (temperature, rain fall, humidity), demography (population density), geography (topography) and DHF alleviation program (free number larva), all the factors give contribution to improve population aedes aegypty mosquito density as risk factorsDHF cases With the ecology study design, using ArcView GIS, this research purpose to spatial analysis risk factors DHF cases, to judgment decesion making as communication process to remove the cases, base of region in south sumatra provinve, cases and determinant collected between 2003-2007. Results of research from correlation with spearman rho analysis recognized direction relation betwen DHF cases and determinant factors like with population density, climatic factors like rain fall and humidity detected positive relation direction, with topography, temperature and DHF cases alleviation program (free number larva) detected negative relation direction For sugestion to program and cases management plan be better, according to diseases management base of region concept, with the result that cases no any more problem with public health.